Fe(3)O(4) nanoparticles on graphene oxide sheets for isolation and ultrasensitive amperometric detection of cancer biomarker proteins - Sharafeldin, Mohamed (Biosens Bioelectron, 2016)
Ultrasensitive mediator-free electrochemical detection for biomarker proteins was achieved at low cost using a novel composite of Fe(3)O(4) nanoparticles loaded onto graphene oxide (GO) nanosheets (Fe(3)O(4)@GO). This paramagnetic Fe(3)O(4)@GO composite (1 μm size range) was decorated with antibodies against prostate specific antigen (PSA) and prostate specific membrane antigen (PSMA), and then used to first capture these biomarkers and then deliver them to an 8-sensor detection chamber of a microfluidic immunoarray. Screen-printed carbon sensors coated with electrochemically reduced graphene oxide (ERGO) and a second set of antibodies selectively capture the biomarker-laden Fe(3)O(4)@GO particles, which subsequently catalyze hydrogen peroxide reduction to detect PSA and PSMA. Accuracy was confirmed by good correlation between patient serum assays and enzyme-linked immunosorbent assays (ELISA). Excellent detection limits (LOD) of 15 fg/mL for PSA and 4.8 fg/mL for PSMA were achieved in serum. The LOD for PSA was 1000-fold better than the only previous report of PSA detection using Fe(3)O(4). Dynamic ranges were easily tunable for concentration ranges encountered in serum samples by adjusting the Fe(3)O(4)@GO Concentration. Reagent cost was only $0.85 for a single 2-protein assay.